Quasi-Complemented BE-Algebras - Kumar V. Venkata; Rao M. Sambasiva; Vali S. Kalesha (Discussiones Mathematicae - General Algebra and Applications, 2021)
The concept of O-filters is introduced in commutative BE-algebras. An equivalent condition is derived for every strong regular filter of a BE-algebra to become an O-filter. The concept of quasi-complemented BE-algebras is introduced and also characterized these classes of BE-algebras in terms of dual annihilators. The concept of strong regular filter is introduced and then quasi-complemented BE-algebras and strong BE-algebras are characterized in terms of strong regular filters and O-filters.